Ádám's Oeuvre in the Light of Our Days' Pedagogical Practice (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
Jenő Ádám's oeuvre in the light of our days’ pedagogical practice is still potent. Kodály Zoltán’s principles on music education could have not been realised without the work of Jenő Ádám (1869 - 1982). He published his Iskolai Énekgyűjtemény (Song-collection for Public Schools), which were edited according to the eight school grades of Hungarian schooling system. These volumes contained several novelties for contemporary school-music teachers: the principles of Kodály built up in a complete concept, a very rich song-material, as well as the tool of relative sol-fa. In a more favorable historical and social context, these textbook series could have been much greater impact on Hungarian music-pedagogy. What and how can we transfer Kodály Zoltán’s concept (mediated by Ádám Jenő) to the current pedagogical practice? Is it worth to update Ádám’s school song collection according to the favour, and pedagogical streams of our days? Should the collection rather remain an educational, and historical relic? In my presentation, I try to find possible answers for all these questions.